2020
DOI: 10.1038/s41598-020-76389-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of deep-learning with anomaly detection for a small amount of imbalanced data: discriminating malignant parotid tumors in MRI

Abstract: We hypothesized that, in discrimination between benign and malignant parotid gland tumors, high diagnostic accuracy could be obtained with a small amount of imbalanced data when anomaly detection (AD) was combined with deep leaning (DL) model and the L2-constrained softmax loss. The purpose of this study was to evaluate whether the proposed method was more accurate than other commonly used DL or AD methods. Magnetic resonance (MR) images of 245 parotid tumors (22.5% malignant) were retrospectively collected. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…There have also been several reports on characterizing PGTs using deep learning. For example, Matsuo et al [ 22 ] reported that the deep learning method could discriminate benign and malignant PGTs in MRI images, with an AUC of 0.86. Gabelloni et al [ 24 ] used magnetic resonance radiomics to discriminate PGTs, with results showing that radiomics analysis had a high diagnostic performance in pleomorphic adenomas and malignant tumors (sensitivity, specificity, and diagnostic accuracy of 0.66, 0.87, and 0.80, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…There have also been several reports on characterizing PGTs using deep learning. For example, Matsuo et al [ 22 ] reported that the deep learning method could discriminate benign and malignant PGTs in MRI images, with an AUC of 0.86. Gabelloni et al [ 24 ] used magnetic resonance radiomics to discriminate PGTs, with results showing that radiomics analysis had a high diagnostic performance in pleomorphic adenomas and malignant tumors (sensitivity, specificity, and diagnostic accuracy of 0.66, 0.87, and 0.80, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that intra/inter-tumoral heterogeneity and overlap of ADC values between BT and MT could be overcome by making a whole-tumor analysis ( 30 , 31 , 43 ). Previously, Ma et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we experimented with two different preprocessing methods to convert the MRI images to eligible CNN input format, to take full advantage of the pre‐trained networks. To briefly sum, the MRI images were resized to 224 × 224 according to the input requirement of Resnet‐18, then converted to RGB format in one of the two following methods. In the single‐modal paradigm, the same MRI sequence served as reiterated input of RGB channels. In the multi‐modal paradigm, compatible modalities were combined, such as T1, T2 and CE‐T1, so that each MRI sequence served as the channel input of individual RGB channels 17 …”
Section: Methodsmentioning
confidence: 99%